2021
DOI: 10.32598/ijpcp.27.2.3535.1
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Factors as Determinants of Suicidal Behaviors Among Adults in Nigeria

Abstract: Objective Suicidal behaviour is seen in the context of a variety of mental disorders and while many believe that, suicide has become a serious matter in both developed and developing countries. This study aimed to evaluate the associated factors of suicidal ideation (SI) and attempt (SA) among Nigerian adults. Method The data were collected from Federal Medical Center Birnin Kebbi and the Ministry of Health and Welfare in Kebbi State, a nationally representative sample recruited using a multi-stage clustered p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The success of commanders in proper interaction with conscripts greatly depends on their leadership abilities [9]. Another effective factor is low economic-social status of soldiers [11,12]. Stack [11] and Argungu et al [12] showed that low income level is significantly related to suicide rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The success of commanders in proper interaction with conscripts greatly depends on their leadership abilities [9]. Another effective factor is low economic-social status of soldiers [11,12]. Stack [11] and Argungu et al [12] showed that low income level is significantly related to suicide rate.…”
Section: Introductionmentioning
confidence: 99%
“…Another effective factor is low economic-social status of soldiers [11,12]. Stack [11] and Argungu et al [12] showed that low income level is significantly related to suicide rate. Suicide is not an instant decision.…”
Section: Introductionmentioning
confidence: 99%